2020
DOI: 10.1002/solr.202000048
|View full text |Cite
|
Sign up to set email alerts
|

All Antimony Chalcogenide Tandem Solar Cell

Abstract: A proof‐of‐concept tandem solar cell using Sb2S3 and Sb2Se3 as top and bottom cell absorber materials is demonstrated. The bandgaps of Sb2S3 and Sb2Se3 are 1.74 and 1.22 eV, perfectly satisfying the requirement of tandem solar cells. The application of few‐layer graphene enables high transmittance and excellent interfacial contact in the top subcell. By controlling the thickness of the top cell for maximizing the spectral application, the tandem device delivers a power conversion efficiency of 7.93%, which out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 22 publications
0
57
0
Order By: Relevance
“…[85] Their combination as top and bottom cell materials could lead to a cost-effective, stable, and environmentally friendly approach for tandem cells. In this regard, Zhang et al [166] demonstrated a proof-of-concept of all antimony chalcogenide 4T tandem solar cell in 2020. They utilized Sb 2 S 3 and Sb 2 Se 3 as top and bottom cells, respectively, as shown in Figure 14d.…”
Section: (21 Of 28)mentioning
confidence: 99%
See 2 more Smart Citations
“…[85] Their combination as top and bottom cell materials could lead to a cost-effective, stable, and environmentally friendly approach for tandem cells. In this regard, Zhang et al [166] demonstrated a proof-of-concept of all antimony chalcogenide 4T tandem solar cell in 2020. They utilized Sb 2 S 3 and Sb 2 Se 3 as top and bottom cells, respectively, as shown in Figure 14d.…”
Section: (21 Of 28)mentioning
confidence: 99%
“…Reproduced with permission. [166] Copyright 2020, Wiley-VCH. e) EQE curve of Sb 2 S 3 /Sb 2 Se 3 double junction solar cells.…”
Section: Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some simulations have implied that the high interfacial defect density and poor carrier transportation drastically limit the device performance of Sb 2 S 3 -based photovoltaics; thus, the present efficiency can be improved by controlling the orientation of Sb 2 S 3 films [44,[63][64][65][66]. Moreover, in 2020, Zhang et al demonstrated a proof-of-concept four-terminal tandem device with a 7.93% efficiency using Sb 2 Se 3 and Sb 2 S 3 solar cells as the bottom and top subcells [67]. This attempt implied that Sb 2 S 3 has the potential for application in tandem solar cells.…”
Section: Potential Candidates As Top Cell For Si-based Tandemsmentioning
confidence: 99%
“…Hence, and owing to these wonderful properties, they are very suitable for producing window layers and economical absorbers for the solar cells [13]. It is worth noting that, the fabrication of the window layers require a semiconducting material that has a wide band gap ( 3.5 eV -3.8 eV) and of higher transmittance [14]. These unique conditions have been exhibited in the metal oxides, such as ZnO, SnO2, and In2O3, which have good efficiency to make as window layers of solar cells [15].…”
Section: Introductionmentioning
confidence: 99%